NLRP3 and ASC suppress lupus-like autoimmunity by driving the immunosuppressive effects of TGF-β receptor signalling. Issue 12 (18th August 2014) - Lech, Maciej; Lorenz, Georg; Kulkarni, Onkar P; Grosser, Marian O O; Stigrot, Nora; Darisipudi, Murthy N; Günthner, Roman; Wintergerst, Maximilian W M; Anz, David; Susanti, Heni Eka; Anders, Hans-Joachim
Abstract : Objectives: The NLRP3/ASC inflammasome drives host defence and autoinflammatory disorders by activating caspase-1 to trigger the secretion of mature interleukin (IL)-1β/IL-18, but its potential role in autoimmunity is speculative. Methods: We generated and phenotyped Nlrp3 -deficient, Asc -deficient, Il-1r -deficient and Il-18 -deficient C57BL/6-lpr/lpr mice, the latter being a mild model of spontaneous lupus-like autoimmunity. Results: While lack of IL-1R or IL-18 did not affect the C57BL/6-lpr/lpr phenotype, lack of NLRP3 or ASC triggered massive lymphoproliferation, lung T cell infiltrates and severe proliferative lupus nephritis within 6 months, which were all absent in age-matched C57BL/6-lpr/lpr controls. Lack of NLRP3 or ASC increased dendritic cell and macrophage activation, the expression of numerous proinflammatory mediators, lymphocyte necrosis and the expansion of most T cell and B cell subsets. In contrast, plasma cells and autoantibody production were hardly affected. This unexpected immunosuppressive effect of NLRP3 and ASC may relate to their known role in SMAD2/3 phosphorylation during tumour growth factor (TGF)-β receptor signalling, for example, Nlrp3 -deficiency and Asc -deficiency significantly suppressed the expression of numerous TGF-β target genes in C57BL/6-lpr/lpr mice and partially recapitulated the known autoimmune phenotype of Tgf-β1 -deficient mice. Conclusions: These data identify a novel non-canonical immunoregulatory function of NLRP3 and ASC in autoimmunity.